2021
DOI: 10.3390/nano11113109
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Optical and Vibrational Properties of GeS

Abstract: The optical response of bulk germanium sulfide (GeS) is investigated systematically using different polarization-resolved experimental techniques, such as photoluminescence (PL), reflectance contrast (RC), and Raman scattering (RS). It is shown that while the low-temperature (T = 5 K) optical band-gap absorption is governed by a single resonance related to the neutral exciton, the corresponding emission is dominated by the disorder/impurity- and/or phonon-assisted recombination processes. Both the RC and PL sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 32 publications
(73 reference statements)
7
25
0
Order By: Relevance
“…2(b), the Raman active phonon modes A 2 g , B 2 1g and A 3 g are observed in the Stokes range from 1.853 to 1.830 eV. Considering the spectral positions of the Raman lines with respect to the laser excitation energy , the phonon energies correspond to our theoretical calculation and to previous reports [11,29]: 116 cm −1 14.4 meV (A 2 g ), 218 cm − 1 27.0 meV (B 2 1g ), and 243 cm − 1 30.1 meV (A 3 g ). They also exhibit distinct polarization properties.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…2(b), the Raman active phonon modes A 2 g , B 2 1g and A 3 g are observed in the Stokes range from 1.853 to 1.830 eV. Considering the spectral positions of the Raman lines with respect to the laser excitation energy , the phonon energies correspond to our theoretical calculation and to previous reports [11,29]: 116 cm −1 14.4 meV (A 2 g ), 218 cm − 1 27.0 meV (B 2 1g ), and 243 cm − 1 30.1 meV (A 3 g ). They also exhibit distinct polarization properties.…”
Section: Resultssupporting
confidence: 76%
“…Complementary photoluminescence and re ectance experiments determine the energy and polarization of the neutral exciton (X) at the -point of the Brillouin zone. In non-resonant Raman spectra, in agreement with previous reports [11,26], four Raman active modes A 2 g , A 3 g , A 4 g and B 2 1g are observed; however, when the excitation energy is tuned towards the X energy, 18 Raman peaks are resolved, among which 14 have not been reported previously in the backscattering geometry. The phonon modes with the symmetries B 1u 2 , B 2u 2 , B 3u 2 , and B 1u 3 , which are Raman forbidden (dark), are also observed in the optical spectra.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…[15,16] Currently, investigations are underway to modulate the electronic properties of GeS and explore many novel applications. [13,[17][18][19][20][21][22] For example, Kong et al studied the quantum confinement effect on the electronic structure and transport properties of monolayer GeS nanoribbions, and they found that edge-reconstructed GeS nanoribbons are promising for optoelectronics and photocatalytics. [23] Mislav et al reported the transport properties of GeS nanoribbons and the ballistic device performance of sub-4 nm field-effect transistors.…”
Section: Introductionmentioning
confidence: 99%